Learning, Work and Social Responsibility - Evans, Karen. author. aut Link
XVI, 274 p.
Keywords: The political consensus on lifelong learning which marked the end of the 20th century fundamentally reshaped discourses on the role of lifelong learning. In ‘knowledge-based’ economies, we are engaged in a lifelong competition for livelihoods; learning for a living as part of a global learning revolution. The argument (of the author), put simply, revolves around social justice, and active and engaged citizenry. Policies to encourage lifelong learning are based on the view that individuals must learn new things primarily to secure employment in an ever-changing world. The result of these policies has been to open up unsustainable inequalities which ordinary people are unlikely to tolerate for much longer. For politicians, bringing politics closer to the world and aspirations of ordinary people will mean seeking solutions based on broader and fairer forms of meritocracy and bringing work and the pursuit of broader social purposes into a better balance at all levels of the social world.